Polyether sulfone as well as preparation method and application thereof
By optimizing the molecular weight distribution and preparation method of polyethersulfone, the requirements for spinning liquid viscosity, pore formation performance and dialysis effect in hemodialysis membrane applications are solved, and efficient preparation and excellent performance of polyethersulfone products are achieved.
Patent Information
- Application Number
- CN202310973195.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-04
AI Technical Summary
When used in hemodialysis membranes, existing polyethersulfone products are difficult to meet the requirements of viscosity, pore-forming performance and dialysis effect of spinning liquid.
By optimizing the molecular weight distribution of polyethersulfone, the proportion of the high molecular weight portion with a weight average molecular weight greater than 200,000 g/mol is reduced to less than 6%, and a specific preparation method, including the stirring intensity control of the salt forming stage and the polymerization stage, is used to regulate it. The main peak molecular weight and molecular weight distribution of polyethersulfone.
The molecular weight distribution of polyethersulfone products is achieved with a main peak molecular weight between 60,000 and 180,000 g/mol, meeting the application performance requirements of hemodialysis membrane, improving the viscosity and pore-forming performance of the spinning liquid, and ensuring the dialysis effect.
Smart Images

Figure BDA0004376364290000021 
Figure BDA0004376364290000041 
Figure FDA0004376364280000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer material synthesis, and specifically relates to polyethersulfone, a preparation method and application thereof. Background Art
[0002] Polyethersulfone is a type of special engineering plastic with excellent performance. It is a type of sulfone polymer. The main chain contains aromatic groups, sulfone groups and ether bonds. Polyethersulfone has excellent thermal stability, water vapor resistance, flame retardancy and self-extinguishing properties, creep resistance, dimensional stability, mechanical properties, biocompatibility, etc. It is widely used in electronics, automobiles, aviation, kitchen supplies, medical equipment and other fields. With the development of society, the demand for high-performance materials has further increased, and the application range of polyethersulfone is becoming wider and wider.
[0003] Currently, conventional sulfone polymers are prepared by polycondensation of dihydroxy aromatic monomers (bisphenol A, biphenol, bisphenol S, etc.) and dichloro aromatic monomers (dichlorodiphenyl sulfone) in the presence of a salt-forming agent. However, compared with bisphenol A and biphenol, the monomer bisphenol S of polyethersulfone is more acidic and forms phenol salts with a salt-forming agent at a faster rate, resulting in the prepared polyethersulfone products affecting the viscosity, pore-forming properties and dialysis effect of the spinning solution when used in hemodialysis membranes.
[0004] CN115028837A discloses an aromatic sulfone polymer, wherein the peak area S of the polymer chain having a molecular weight greater than 150,000 g / mol is M150000 The peak area of the total polymer chain S M The proportion is between 7-10%. This aromatic sulfone polymer can be used to prepare molded plastic parts, ultrafiltration membranes, coatings, etc., but when applied to hemodialysis membranes, it still has the above-mentioned defects and is difficult to meet application requirements.
[0005] Therefore, it is necessary to develop polyethersulfone products that meet the performance requirements for application scenarios such as hemodialysis membranes. Summary of the invention
[0006] The inventors of the present application optimized the molecular weight distribution of polyethersulfone and reduced the proportion of the high molecular weight part (weight average molecular weight > 200,000 g / mol) in polyethersulfone to a specific range. They unexpectedly found that the prepared polyethersulfone product can meet the application performance requirements of hemodialysis membrane, thereby completing the present invention.
[0007] In order to achieve the above objectives, one object of the present invention is to provide a polyethersulfone product in which the high molecular weight portion (weight average molecular weight not less than 200000 g / mol) accounts for less than 6%, which can meet the application requirements of hemodialysis membranes.
[0008] Another object of the present invention is to provide a method for preparing the polyethersulfone.
[0009] Another object of the present invention is to provide applications of the polyethersulfone product.
[0010] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solution:
[0011] A polyethersulfone, the general structural formula of which is shown in formula (I):
[0012]
[0013] Wherein, the following formula is satisfied: x=A1 / (A1+A2)<6%, preferably, x=A1 / (A1+A2)<5%, more preferably, x=A1 / (A1+A2)<3%;
[0014] Wherein, A1 is the integral area occupied by the weight average molecular weight not less than 200000 g / mol in the GPC spectrum, and A1 is recorded as the high molecular weight peak area; A2 is the integral area occupied by the weight average molecular weight less than 200000 g / mol in the GPC spectrum, and A2 is recorded as the main peak area.
[0015] In a specific embodiment, the weight average molecular weight of the main peak is between 60,000 and 180,000 g / mol, preferably between 80,000 and 145,000 g / mol.
[0016] In a specific embodiment, the molecular weight distribution is less than 2.0, preferably 1.2 to 1.8.
[0017] On the other hand, the preparation method of the aforementioned polyethersulfone comprises the following steps:
[0018] 1) Salt-forming stage: dissolving monomer 1 and monomer 2 in a reaction solvent, then adding a salt-forming agent and a water-carrying agent into a reaction kettle under stirring, heating to reflux for reaction, and then raising the temperature to completely evaporate the water-carrying agent in the reaction kettle; wherein at least one of the monomer 1, monomer 2 and the salt-forming agent is added in batches;
[0019] 2) Polymerization stage: After the polymerization reaction, the stirring speed is reduced, and then a capping agent is added for capping. The reaction fluid is then filtered, crushed, washed with water, and vacuum dried to obtain polyether sulfone.
[0020] In a specific embodiment, the monomer 1 and / or the salt-forming agent are added in batches.
[0021] In a preferred embodiment, the monomer 1 and / or the salt-forming agent are added in three batches; preferably, they are added in three batches at the beginning of the reaction, at reflux for 1 hour, and at reflux for 3 hours.
[0022] In a specific embodiment, the batch addition is equal-proportional batch addition or non-equal-proportional batch addition.
[0023] In a specific embodiment, the salt formation stage is heated to 140-220° C. for reflux reaction for 2-6 hours, and the polymerization stage is reacted at 160-230° C. for 2-48 hours.
[0024] In a specific embodiment, the first monomer is bisphenol S, and the second monomer is one or more of dichlorodiphenyl sulfone and difluorodiphenyl sulfone.
[0025] In a specific embodiment, the salt-forming agent is one or more of sodium hydroxide, potassium hydroxide, cesium hydroxide, potassium carbonate, sodium carbonate, cesium carbonate, potassium bicarbonate, and sodium bicarbonate.
[0026] In a specific embodiment, the reaction solvent is any one of dimethyl sulfoxide, dimethyl sulfone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and sulfolane.
[0027] In a specific embodiment, the water-carrying agent is one or more of toluene, xylene, o-xylene, chlorobenzene, and mesitylene.
[0028] In a specific embodiment, the capping agent is methyl chloride.
[0029] In a specific embodiment, the tip linear velocity of the stirring blade in the salt formation stage is between 6 and 10 m / s, and the tip linear velocity of the stirring blade in the polymerization stage is between 2 and 4 m / s.
[0030] On the other hand, the aforementioned polyethersulfone or the polyethersulfone prepared by the aforementioned polyethersulfone preparation method is used in the fields of electronics and electrical, automobiles and aviation, kitchen supplies, and medical devices, preferably in hemodialysis membranes.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The polyethersulfone product of the present invention has a narrow molecular weight distribution, and the high molecular weight peak area with a weight average molecular weight of not less than 200,000 g / mol in the GPC spectrum accounts for less than 6%, which can meet the performance requirements of application scenarios such as hemodialysis membranes.
[0033] (2) The preparation method of the present invention effectively solves the key problems existing in the polymerization of polyethersulfone. The molecular weight of the main peak of polyethersulfone can be adjusted to a weight average molecular weight between 60,000 and 180,000 g / mol, which has certain guiding significance for the industrial production of sulfone series products. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the GPC spectrum of the polyethersulfone prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein.
[0036] A polyethersulfone, the general structural formula of which is shown in formula (I):
[0037]
[0038] Satisfies the following formula: x=A1 / (A1+A2)<6%, such as x<5%, x<4%, x<3%, x<2%, x<1%, etc., preferably x=A1 / (A1+A2)<5%, more preferably x=A1 / (A1+A2)<3%;
[0039] Wherein, A1 is the integral area occupied by the weight average molecular weight not less than 200000 g / mol in the GPC spectrum, and A1 is recorded as the high molecular weight peak area; A2 is the integral area occupied by the weight average molecular weight less than 200000 g / mol in the GPC spectrum, and A2 is recorded as the main peak area.
[0040] The GPC test conditions in the present invention are as follows: N,N-dimethylformamide is used as the mobile phase with a flow rate of 1.0 mL / min, polystyrene is used as the reference standard, and chromatographic columns Shodex KD-802, KD-803, and KD-804 are used in series.
[0041] The polyethersulfone of the present invention has a main peak weight average molecular weight of 60000-180000 g / mol, for example, 60000 g / mol, 70000 g / mol, 80000 g / mol, 90000 g / mol, 100000 g / mol, 110000 g / mol, 120000 g / mol, 130000 g / mol, 140000 g / mol, 150000 g / mol, 160000 g / mol, 170000 g / mol, 180000 g / mol, etc., preferably 80000-145000 g / mol. Meanwhile, the molecular weight distribution is less than 2.0, for example, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, etc., preferably 1.2-1.8. Under the premise that the weight average molecular weight and molecular weight distribution are determined, the degree of polymerization n of the polyethersulfone in formula (I) can also be determined accordingly, for example, n is 100 to 800, preferably 300 to 600.
[0042] The polyethersulfone with the above structural characteristics has a very small proportion of the high molecular weight portion with a weight average molecular weight of not less than 200,000 g / mol, for example, less than 6%, preferably less than 5%, more preferably less than 3%, and has a narrow molecular weight distribution. Therefore, when the prepared polyethersulfone product is used for hemodialysis membrane, the effect on the viscosity and pore-forming properties of the spinning solution will be relatively small, and ultimately the dialysis effect will not be affected.
[0043] Those skilled in the art will appreciate that any polyethersulfone having the above structural characteristics can exhibit substantially the same performance when applied to hemodialysis membranes, regardless of the method used to prepare the polyethersulfone product having such structural characteristics.
[0044] Polyethersulfone is usually prepared by the nucleophilic substitution reaction of bisphenol S salt (sodium salt, potassium salt, etc.) and dichlorodiphenylsulfone, and is terminated by methyl chloride. In order to prepare the polyethersulfone product with the above performance characteristics, the inventors of the present application have found that one of the reasons for the wide molecular weight distribution of polyethersulfone and the high content of the high molecular weight part is that the salt formation rate of bisphenol S and the salt-forming agent is fast, and a large amount of gas is released quickly and in a short time, which easily causes the material to splash and produce the phenomenon of material hanging on the wall, resulting in an imbalance in the monomer ratio and an increase in dead zone, thereby making the molecular weight distribution of polyethersulfone wider. For this reason, the salt formation rate must be controlled to reduce the splashing of the material.
[0045] In addition, another important reason why the molecular weight distribution of polyethersulfone is multimodal is that with the increase of system viscosity, the mass and heat transfer in the system is insufficient and untimely, and hot spots exist. Therefore, it is necessary to increase the stirring intensity, optimize the material circulation in the system, control the stirring intensity at a higher level, and further optimize the material distribution in the system.
[0046] The following is an exemplary preparation method, but it does not constitute any limitation. A preparation method of polyethersulfone comprises the following steps:
[0047] All or part of the monomer 1 and the salt-forming agent are added to the reaction solvent respectively, and then the water-carrying agent is added to the reactor under stirring, and the mixture is heated to 140-220° C. for reflux reaction for 2-6 hours, and the tip linear velocity of the stirring blade is between 6 and 10 m / s; the temperature is increased to completely evaporate the water-carrying agent in the reactor, and then the mixture is reacted at 160-230° C. for 2-48 hours, and the tip linear velocity of the stirring blade is between 2 and 4 m / s, and then a certain amount of end-capping agent is added, and then the reaction liquid is filtered, crushed, washed with water, and vacuum dried to obtain polyethersulfone.
[0048] Among them, the monomer one is bisphenol S, the monomer two is one or more of dichlorodiphenyl sulfone and difluorodiphenyl sulfone, preferably dichlorodiphenyl sulfone; the salt-forming agent is one or more of sodium hydroxide, potassium hydroxide, cesium hydroxide, potassium carbonate, sodium carbonate, cesium carbonate, potassium bicarbonate, sodium bicarbonate, preferably sodium carbonate and / or potassium carbonate; the reaction solvent is one of dimethyl sulfoxide, dimethyl sulfone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and cyclopentane, preferably N-methylpyrrolidone or cyclopentane; the water-carrying agent is one or more of toluene, xylene, o-xylene, chlorobenzene, and mesitylene, preferably xylene; the end-capping agent is methyl chloride.
[0049] In the salt-forming stage, the reaction is heated to 140-220°C for reflux reaction for 2-6 hours. The reflux temperature is, for example, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, etc., and can be set according to the boiling point of the reaction solvent, for example, lower than the boiling point of the reaction solvent; the reflux time is, for example, 2h, 3h, 4h, 5h, 6h, etc., and can be based on the fact that no water is produced.
[0050] In the polymerization stage, the reaction is carried out at 160-230°C for 2-48h. For example, the polymerization reaction temperature is 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, etc., and the polymerization reaction time is 2h, 3h, 4h, 5h, 6h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 48h, etc. In the actual preparation process, the degree of polymerization reaction can also be judged by monitoring indicators such as the viscosity of the reaction system or the current value.
[0051] In the present invention, there is no particular restriction on the amount of each reaction raw material. For example, taking bisphenol S and dichlorodiphenyl sulfone as the reaction raw materials, the amount ratio of bisphenol S to dichlorodiphenyl sulfone is 1:1.0 to 1:1.03, the amount of the salt-forming agent added is 1.05 to 1.3 times the amount of the bisphenol S substance, the amount of the reaction solvent added is such that the solid content of the reaction system reaches 20% to 40%, the amount of the water-carrying agent added is 0.1 to 0.5 of the mass of the reaction solvent, and the amount of the end-capping agent added is 0.02 to 0.1 of the molar amount of the bisphenol S.
[0052] In the present invention, all or part of bisphenol S, dichlorodiphenyl sulfone and / or salt-forming agent are added to the reaction solvent respectively, for example, bisphenol S, dichlorodiphenyl sulfone or salt-forming agent are added in batches, or two of them are added in batches, or the three are added in batches at the same time, wherein the batch addition can be, for example, 3 equal parts or more equal parts or unequal parts multiple times; preferably, for example, they are added in batches at the beginning of the reaction, reflux for 1 hour, and reflux for 3 hours, but not limited to this, for example, they are added in batches at the beginning of the reaction, reflux for 2 hours, and reflux for 4 hours, or at the beginning of the reaction, reflux for 1.5 hours, and reflux for 3.5 hours. In order to improve the reaction efficiency and shorten the reaction time, it is preferred that all the salt-forming agents are added in batches within 5 hours of the reaction.
[0053] In a preferred solution, the stirring intensity in the salt-forming stage and the polymerization stage is further controlled, for example, the tip linear velocity of the stirring paddle in the salt-forming stage is controlled between 6 and 10 m / s, such as 6 m / s, 7 m / s, 8 m / s, 9 m / s, 10 m / s, etc.; the tip linear velocity of the stirring paddle in the polymerization stage is controlled between 2 and 4 m / s, such as 2 m / s, 2.5 m / s, 3 m / s, 3.5 m / s, 4 m / s, etc. By controlling the tip linear velocity of the stirring paddle in the salt-forming stage and the polymerization stage, the material circulation in the system is optimized, and the material distribution in the system is further optimized, so that the molecular weight distribution is narrower.
[0054] The reaction conditions described in the present invention are all nitrogen atmosphere, the reaction container is baked and dried to remove water, and is vacuumed and filled with nitrogen multiple times. The steps not specifically described in the present invention can refer to the prior art, such as reaction liquid filtration, crushing, water washing, vacuum drying and other processes, which can be achieved by conventional technical means in the art.
[0055] The present invention is further explained below by more specific examples, but does not constitute any limitation.
[0056] The test methods and test conditions used in the following examples are:
[0057] GPC was used for molecular structure characterization, using N,N-dimethylformamide as the mobile phase with a flow rate of 1.0 mL / min, polystyrene as the reference standard, and chromatographic columns Shodex KD-802, KD-803, and KD-804 in series.
[0058] Example 1
[0059] 2002g of bisphenol S, 2320g of dichlorodiphenyl sulfone and 424g of potassium carbonate were added to 6894g of cyclobutane sulfone in sequence, and then 1380g of xylene was added to the reactor. The blade tip linear velocity of the stirring paddle in the salt-forming stage was 6m / s. The xylene was heated to 180°C and refluxed with water. After reflux for 1h and 3h, 423g of potassium carbonate was added respectively. When no water was produced, the temperature was increased to completely evaporate the xylene in the reactor. The blade tip linear velocity of the stirring paddle was adjusted to 2m / s, and then the reaction was carried out at 220°C for 3.5h. After cooling to 150°C, methyl chloride was introduced for 30min. Finally, the reaction liquid was filtered, crushed, washed with water and vacuum dried to obtain polyether sulfone.
[0060] Molecular structure characterization: GPC spectrum such as Figure 1 As shown, the weight average molecular weight of the main peak of the prepared polyethersulfone is 137200 g / mol, the molecular weight distribution is 1.94, and x=3.4%.
[0061] Example 2
[0062] The difference from Example 1 is that N-methylpyrrolidone is used as the solvent, the polymerization temperature is 190° C., and the polymerization time is 6 h.
[0063] Molecular structure characterization: The weight average molecular weight of polyethersulfone is 139350 g / mol, the molecular weight distribution is 1.88, and x=4.8%.
[0064] Example 3
[0065] The difference from Example 1 is that sodium carbonate is used as the salt-forming agent, and sodium carbonate is added in three equal portions, 340 g, 339 g, and 339 g of sodium carbonate are added at the beginning, at reflux for 1 h, and at reflux for 3 h, respectively.
[0066] Molecular structure characterization: The weight average molecular weight of the main peak of polyethersulfone is 142200 g / mol, the molecular weight distribution is 1.82, and x=4.3%.
[0067] Example 4
[0068] The difference from Example 1 is that a mixed salt-forming agent of potassium carbonate (663 g) / sodium carbonate (509 g) is used, and 221 g potassium carbonate / 170 g sodium carbonate, 221 g potassium carbonate / 169 g sodium carbonate, and 221 g potassium carbonate / 169 g sodium carbonate are added at the beginning of the reaction, at reflux for 1 h, and at reflux for 3 h, respectively.
[0069] Molecular structure characterization: The weight average molecular weight of the main peak of polyethersulfone is 140020 g / mol, the molecular weight distribution is 1.78, and x=2.9%.
[0070] Example 5
[0071] The difference from Example 1 is that: a process of adding bisphenol S in three equal portions is adopted, with 668 g, 667 g, and 667 g of bisphenol S added at the beginning of the reaction, at reflux for 1 hour, and at reflux for 3 hours, respectively.
[0072] Molecular structure characterization: The weight average molecular weight of polyethersulfone is 139000 g / mol, the molecular weight distribution is 1.65, and x=3.1%.
[0073] Example 6
[0074] The difference from Example 1 is that: a process of adding potassium carbonate and bisphenol S in unequal portions three times is adopted, with 635g potassium carbonate / 1001g bisphenol S, 318g potassium carbonate / 501g bisphenol S, and 317g potassium carbonate / 500g bisphenol S being added at the beginning of the reaction, at reflux for 1h, and at reflux for 3h, respectively.
[0075] Molecular structure characterization: The weight average molecular weight of polyethersulfone is 141300 g / mol, the molecular weight distribution is 1.72, and x=2.6%.
[0076] Example 7
[0077] The difference from Example 6 is that the tip linear velocity of the stirring blade in the salt-forming stage is 10 m / s.
[0078] Molecular structure characterization: The weight average molecular weight of polyethersulfone is 140240 g / mol, the molecular weight distribution is 1.72, and x=1.1%.
[0079] Example 8
[0080] The difference from Example 1 is that the polymerization time is extended to 6 hours.
[0081] Molecular structure characterization: The weight average molecular weight of polyethersulfone is 179010 g / mol, the molecular weight distribution is 1.92, and x=5.2%.
[0082] Example 9
[0083] The difference from Example 1 is that the tip linear velocity of the stirring blade during the entire reaction stage is 6 m / s.
[0084] Molecular structure characterization: The weight average molecular weight of polyethersulfone is 140230 g / mol, the molecular weight distribution is 1.84, and x=5.7%.
[0085] Comparative Example 1
[0086] The difference from Example 1 is that all materials are added at once at the beginning of the reaction, and the tip linear speed of the stirring blade is 2 m / s during the entire reaction process.
[0087] Molecular structure characterization: The weight average molecular weight of the main peak of polyethersulfone is 138400 g / mol, the molecular weight distribution is 2.11, and the main peak area accounts for x=22.8%.
[0088] Comparative Example 2
[0089] The difference from Example 1 is that all materials are added at once at the beginning of the reaction, and other conditions are exactly the same.
[0090] Molecular structure characterization: The weight average molecular weight of the main peak of polyethersulfone is 139760 g / mol, the molecular weight distribution is 2.05, and x=13.3%.
[0091] In the polyethersulfone product prepared in the embodiment of the present invention, the high molecular weight peak area with a weight average molecular weight greater than or equal to 200,000 g / mol accounts for less than 6%, and the weight average molecular weight of the main peak of polyethersulfone is between 60,000 and 180,000 g / mol. According to feedback from downstream customers, the polyethersulfone product with this structural feature can meet the application performance requirements of hemodialysis membranes.
Claims
1. A polyethersulfone, the general structural formula of which is shown in formula (I): It is characterized in that Satisfies the following formula: x=A1 / (A1+A2)<6%, preferably, x=A1 / (A1+A2)<5%, more preferably, x=A1 / (A1+A2)<3%; Wherein, A1 is the integral area occupied by the weight average molecular weight not less than 200000 g / mol in the GPC spectrum, and A1 is recorded as the high molecular weight peak area; A2 is the integral area occupied by the weight average molecular weight less than 200000 g / mol in the GPC spectrum, and A2 is recorded as the main peak area.
2. The polyethersulfone according to claim 1, characterized in that The weight average molecular weight of the main peak is between 60,000 and 180,000 g / mol, preferably between 80,000 and 145,000 g / mol.
3. The polyethersulfone according to claim 1 or 2, characterized in that The molecular weight distribution is less than 2.0, preferably 1.2 to 1.
8.
4. The method for preparing polyethersulfone according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Salt-forming stage: dissolving monomer 1 and monomer 2 in a reaction solvent, then adding a salt-forming agent and a water-carrying agent into a reaction kettle under stirring, heating to reflux for reaction, and then raising the temperature to completely evaporate the water-carrying agent in the reaction kettle; wherein at least one of the monomer 1, monomer 2 and the salt-forming agent is added in batches; 2) Polymerization stage: After the polymerization reaction, the stirring speed is reduced, and then a capping agent is added for capping. The reaction fluid is then filtered, crushed, washed with water, and vacuum dried to obtain polyether sulfone.
5. The method for preparing polyethersulfone according to claim 4, characterized in that: The monomer 1 and / or salt-forming agent are added in batches; preferably in three batches; preferably, added in three batches at the beginning of the reaction, at reflux for 1 hour, and at reflux for 3 hours.
6. The method for preparing polyethersulfone according to claim 5, characterized in that: The batch addition can be equal proportion batch addition or non-equal proportion batch addition.
7. The method for preparing polyethersulfone according to claim 4, characterized in that: The salt formation stage is heated to 140-220°C for reflux reaction for 2-6 hours, and the polymerization stage is reacted at 160-230°C for 2-48 hours.
8. The method for preparing polyethersulfone according to any one of claims 4 to 7, characterized in that: The first monomer is bisphenol S, and the second monomer is one or more of dichlorodiphenyl sulfone and difluorodiphenyl sulfone; Preferably, the salt-forming agent is one or more of sodium hydroxide, potassium hydroxide, cesium hydroxide, potassium carbonate, sodium carbonate, cesium carbonate, potassium bicarbonate, and sodium bicarbonate; Preferably, the reaction solvent is any one of dimethyl sulfoxide, dimethyl sulfone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and sulfolane; Preferably, the water-carrying agent is one or more of toluene, xylene, o-xylene, chlorobenzene, and mesitylene; Preferably, the end-capping agent is methyl chloride.
9. The method for preparing polyethersulfone according to any one of claims 4 to 8, characterized in that: The blade tip linear velocity of the stirring paddle in the salt formation stage is between 6 and 10 m / s, and the blade tip linear velocity of the stirring paddle in the polymerization stage is between 2 and 4 m / s.
10. Use of the polyethersulfone according to any one of claims 1 to 3 or the polyethersulfone prepared by the method for preparing polyethersulfone according to any one of claims 4 to 8 in the fields of electronics and electrical, automobiles and aviation, kitchen supplies, and medical devices, preferably in hemodialysis membranes.
Citation Information
Patent Citations
Aromatic sulfone polymer and preparation method of aromatic sulfone polymer
CN110527091A
Preparation method of polyether sulfone
CN112851942A
Preparation method of double-terminated polysulfone
CN113388112A
Production of polyether sulfone
JP1993163352A
Polysulfone-based permselective hollow fiber membrane bundle and blood purifier
JP2006230458A